2011
DOI: 10.1007/s12022-011-9149-8
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin and Dopamine Receptor Profile of Gastroenteropancreatic Neuroendocrine Tumors: An Immunohistochemical Study

Abstract: Somatostatin and its synthetic analogs act through five specific somatostatin receptors (sstr1-5), found on the cell membrane of various tumors, including endocrine ones. Dopamine--a known neurotransmitter--acts through five membranous dopamine receptors (D1R-D5R) which have recently been found to be expressed in endocrine tumors. We evaluated the immunohistochemical expression of the sstrs and D2R in a large series of gastroenteropancreatic neuroendocrine tumors (GEP-NETs). A total of 22 (28.94%) well-differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
3
20
0
1
Order By: Relevance
“…Two spliced variants of SSTR2 (SSTR2A and SSTR2B) have been found, with SSTR2A having the highest expression and the greatest relevance from a biological and clinical perspective. Somatostatin and its synthetic analogues (octreotide and lanreotide) act through the five specific SSTRs found on the cell membranes of various tumours, including GEP-NET (Diakatou et al 2011). The first step of the signalling cascade following agonist stimulation is the internalisation of the SSTR (Scott et al 2002).…”
Section: Somatostatin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two spliced variants of SSTR2 (SSTR2A and SSTR2B) have been found, with SSTR2A having the highest expression and the greatest relevance from a biological and clinical perspective. Somatostatin and its synthetic analogues (octreotide and lanreotide) act through the five specific SSTRs found on the cell membranes of various tumours, including GEP-NET (Diakatou et al 2011). The first step of the signalling cascade following agonist stimulation is the internalisation of the SSTR (Scott et al 2002).…”
Section: Somatostatin Receptorsmentioning
confidence: 99%
“…Dopamine, a well-characterised neurotransmitter, acts through five dopamine receptors (D1-D5) that are expressed in endocrine tumours (Diakatou et al 2011). The D2 receptor is the most relevant from a clinical perspective.…”
Section: Other Gpcrsmentioning
confidence: 99%
“…The SSTR subtypes 1-5 are targeted via somatostatin receptor scintigraphy (SRS) and long-acting somatostatin analogues (SAs) [5,6] and/or peptide receptor radionuclide treatment [7] for diagnostic and therapeutic purposes, respectively. To date, only a limited number of studies have demonstrated the expression of SSTR subtypes other than SSTR2A in NETs with divergent results, possibly due to differences in the methodology applied [8,9,10,11,12,13,14,15,16,17,18]. Data concerning LCs are even more sparse and inconsistent [15,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to heterodimerization between SSTRs and DRs that result in new oligomeric receptor entities with enhanced functional activity [28]. To date, only few studies have investigated the expression of DR2 in NETs, and only two included a small number of LCs [11,29,30,31,32]. In addition, the co-expression of SSTRs and DRs has not been examined in LCs.…”
Section: Introductionmentioning
confidence: 99%
“…Such compounds have been shown to be more effective in suppressing growth hormone and prolactin secretion from cultured human growth hormone-secreting pituitary tumors than monoreceptor ligands alone [13,14,15]. As the majority of GEP-NETs coexpress SSTRs and D2R, such compounds might offer novel therapeutic opportunities [16,17]. …”
Section: Introductionmentioning
confidence: 99%